Design and validation of a diagnostic test instrument for identifying misconceptions in basic physics - Zahriah, Zahriah; Annisa, Fera; Ahmad, Nur Hidayah Binti; Fahira, Adinda (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2025)
Misconceptions are a classic problem experienced by students in learning which can affect academic achievement, and difficulty understanding advanced physics concepts, and this has the potential to inherit the same mistakes when students become teachers. The unavailability of instruments to identify misconceptions makes it difficult for lecturers to explore student misconceptions, so it is necessary to develop a set of diagnostic test instruments. This research aims to design and test the feasibility of a three-level diagnostic test instrument which will then be used as a tool to identify student misconceptions in the Basic Physics course. This research method is research and development (R&D) of the Plomp model with stages: 1) preliminary investigation, 2) design, 3) realization/construction, 4) testing, evaluation, and revision, and 5) implementation. Data collection techniques use questionnaires and tests, with research instruments in the form of validation sheets and diagnostic test questions. The content validity data analysis technique uses a percentage scale of feasibility categories based on expert judgment and construct validity testing using item analysis software version 2.03. The results of testing the feasibility of the diagnostic test instrument in terms of content validity obtained an overall percentage of 97.21%, while the construct validity test found that 75% of the questions were suitable for use. Thus, it can be concluded that the diagnostic test instrument that has been designed is suitable for use and makes a significant contribution to identifying student misconceptions, as well as helping to improve the quality of education, especially in physics learning, and supporting better academic goals.